SAT0410 Secukinumab Improves Physical Function and Quality of Life in Patients with Active Ankylosing Spondylitis: 2-Year Data from Measure 1, A Phase 3 Randomised Trial. (15th July 2016) - Emery, P.; Baeten, D.; Deodhar, A.; Wei, A.; Geusens, P.; Talloczy, Z.; Gong, Y.; Porter, B.; ,
Abstract : Background: Ankylosing spondylitis (AS) has significant adverse effects on an individual's health status. 1 Secukinumab, an interleukin (IL)-17A inhibitor, improved signs and symptoms and patient-reported outcomes (PROs) over 52 weeks (wks) in the randomised, double-blind, placebo (PBO)-controlled, Phase 3 MEASURE 1 study (NCT01358175 ). 2, 3 Objectives: To evaluate the effect of secukinumab on disease activity, pain, physical function, fatigue, and general and AS-specific quality of life (QoL) measures over 104 wks. Methods: 371 adults with active AS were randomised to receive secukinumab 10 mg/kg i.v. at baseline (BL), Wks 2 and 4, and then s.c. 150 mg (IV→150 mg) or 75 mg (IV→75 mg) every 4 wks from Wk 8, or PBO. At Wk 16, PBO-treated patients (pts) were re-randomised to receive secukinumab 150 mg or 75 mg s.c. from Wk 16 (non-responders) or Wk 24 (responders). PROs assessed included: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI); Short Form-36 physical and mental component summaries (SF-36 PCS and SF-36 MCS, respectively); AS Quality of Life (ASQoL); patient's global assessment of disease activity; patient's assessment of total spinal pain; patient's assessment of nocturnal pain; Bath Ankylosing Spondylitis Functional Index (BASFI); Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue); and EuroQoL-5-dimension health status questionnaire (EQ-5D). BASDAI, SF-36 PCS and ASQoL were predefined secondary endpoints and are reported using a mixed-effect model repeated measures (MMRM) analysis. Other PROs and analyses by prior anti-tumor necrosis factor (anti-TNF) therapy use were exploratory endpoints and are reported as observed data (Wk 104). Results: 97/125 (77.6%) and 103/124 (83.1%) pts randomised to IV→150 mg and IV→75 mg, respectively, completed 104 wks of treatment. The improvements in BASDAI, SF-36 PCS and MCS, ASQoL, BASFI, and FACIT-Fatigue achieved with secukinumab at Wk 52 were sustained at Wk 104, with mean changes from BL being greater than minimum clinically important differences (Table ). Improvements were also observed in patient's global assessment of disease activity, total spinal pain, nocturnal pain, and EQ-5D. Sustained improvements were observed regardless of prior anti-TNF use. In anti–TNF-naïve pts, mean changes from baseline at Wk 104 with secukinumab IV→150 mg and IV→75 mg were: −3.5 and −3.1, respectively, for BASDAI; 8.4 and 7.4 for SF-36 PCS; and −5.0 and −4.4 for ASQoL. Corresponding changes in anti-TNF-IR pts, were: −3.2 and −2.9 (BASDAI); 6.9 and 7.6 (SF-36 PCS); and −4.1 and −5.1 (ASQoL). Conclusions: In pts with active AS, secukinumab provided sustained improvements through 2 years in PROs including disease activity, pain, physical function, fatigue, as well as general and AS-specific measures of QoL. References: Sieper J et al. Ann Rheum Dis 2002;61:iii8–18 Deodhar A et al. Arthritis Rheum 2014;66:S233 Baeten D et al. N Engl J Med 2015;373:2534–48 Disclosure of Interest: P. Emery Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Roche, UCB, D. Baeten Grant/research support from: Boehringer Ingelheim, Janssen, MSD, Novartis, Pfizer, AbbVie, BMS, Eli Lilly, Roche, UCB, A. Deodhar Grant/research support from: AbbVie, Amgen, Boehringer Ingelheim, Janssen, Novartis, Pfizer, UCB, A. Wei Grant/research support from: Abbvie, BMS, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer, Sanofi-Aventis, TSH Taiwan, and UCB, Consultant for: Abbvie, BMS, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer, Sanofi-Aventis, TSH Taiwan, and UCB, P. Geusens Grant/research support from: participation in clinical studies, boards, Speakers bureau: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Z. Talloczy Shareholder of: Novartis, Employee of: Novartis, Y. Gong Employee of: Novartis, B. Porter Shareholder of: Novartis, Employee of: Novartis